Body composition adaptations to lower-body plyometric training: a systematic review and meta-analysis - Rodrigo Ramirez-Campillo; Felipe García-Pinillos; Pantelis T. Nikolaidis; Filipe Clemente; Paulo Gentil; Antonio García-Hermoso (Termedia Publishing House, 2021)
The aim of this meta-analysis was to explore the effects of plyometric jump training (PJT) on body composition parameters among males. Relevant articles were searched in the electronic databases PubMed, MEDLINE, WOS, and SCOPUS, using the key words "ballistic", "complex", "explosive", "force-velocity", "plyometric", "stretch-shortening cycle", "jump", "training", and "body composition". We included randomized controlled trials (RCTs) that investigating the effects of PJT in healthy male's body composition (e.g., muscle mass; body fat), irrespective of age. From database searching 21 RCTs were included (separate experimental groups = 28; pooled number of participants = 594). Compared to control, PJT produced significant increases in total leg muscle volume (small ES = 0.55, p = 0.009), thigh muscle volume (small ES = 0.38, p = 0.043), thigh girth (large ES = 1.78, p = 0.011), calf girth (large ES = 1.89, p = 0.022), and muscle pennation angle (small ES = 0.53, p = 0.040). However, we did not find significant difference between PJT and control for muscle cross-sectional area, body fat, and skinfold thickness. Heterogeneity remained low-to-moderate for most analyses, and using the Egger's test publication bias was not found in any of the analyses (p = 0.300-0.900). No injuries were reported among the included studies. PJT seems to be an effective and safe mode of exercise for increasing leg muscle volume, thigh muscle volume, thigh and calf girth, and muscle pennation angle. Therefore, PJT may be effective to improve muscle size and architecture, with potential implications in several clinical and sport-related contexts.